Therapeutic approach for osteoporotic animal model by bone marrow mesenchymal stem cells - Abdullah S. M. Aljohani, Abdel Kader A. Zaki, Waleed Al Abdulmonem, Zafar Rasheed, Fahad A. Alhumaydhi, Faten A. M. Abo-Aziza (Journal of Applied Pharmaceutical Science, 2021)
Osteoporosis (OP) is a common debilitating metabolic bone disorder manifested by poor mineral density and deteriorated skeleton. Stem cell therapies are being considered as alternative therapeutic modalities. This study determined the therapeutic potential of mesenchymal stem cell (MSC) application in osteoporotic rats. To achieve this, an OP animal model was developed through ovariectomy and glucocorticoids in rats. MSCs were isolated from the same breed of rats and cultured MSCs were administered to osteoporotic rats via vein injections. After 4 and 8 weeks of MSCs administration, rats were sacrificed and all desired components, including serum and joints, were isolated. The present findings showed that the transplantation of MSCs into osteoporotic rats enhanced osteoblastic differentiation and function reverting OP. Calcium deposition, bone-specific alkaline phosphatase activity, and serum osteocalcin concentration were significantly elevated in MSCs-treated osteoporotic rats (p < 0.05). Notably, their levels were much higher in osteoporotic rats treated for 8 weeks than in those treated for 4 weeks (p < 0.05). Moreover, the histological image of the femur head showed uniform thinning of trabeculae (TB) in osteoporotic rats, resulting in the widening of intertrabecular spaces and disjointed bony ossicles interrupted by virtue of expanded fatty bone marrow spaces. Interestingly, after MSCs treatment, cancellous bone TB appeared normal with red bone marrow. Furthermore, a photomicrograph of osteogenic differentiation of MSCs of MSCs-treated osteoporotic rats showed significantly high scattered red calcified nodules (p < 0.05). In conclusion, this study illustrates that the transplantation of MSCs into osteoporotic rats provides a supplement for bone architecture and enhances osteoblastic differentiation and function, thus reverting OP. This work presents a unique method as a future application for the treatment of human OP.
Keywords: Bone biomarkers, bone marrow, mesenchymal stem cell, osteoporosis, rat model